Сьӧлыктэм сьӧлык: кузьмадёсъёс, веросъёс / Анатолий Перевозчиков - Перевозчиков Анатолий Аркадьевич (Удмуртия, 2017)
Экземпляры: ф.1 (20170920) / Инвентарный номер: 54056 / Цена: / Сис.шифр: 84(2 Рос.=Удм)-44 / Авт.знак: П 27 / ББК: 84(2 Рос.=Удм)-44